(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the essence of information attacks in the context of globalization and digital transformation, as well as their psychological and social impact on the consciousness of young people. The theoretical foundations of the concept of spiritual and moral immunity are highlighted, and the role of family psychology in its formation is revealed. In addition, the influence of gender stereotypes on child upbringing, personality socialization, and the formation of social consciousness is examined through a comprehensive approach. During the research, issues such as media literacy, critical thinking, mechanisms of social control, and pedagogical cooperation are widely discussed, and practical suggestions and recommendations are developed.